Modified Segment Constrained Vector Quantizer Design - Jahromi, Mohammad N. S.; Demirciler, Kemal (IEEE, 2015)
In this paper, we modify the segment constrained vector quantizer (VQ), called Seg-VQ, by keeping the first segment length fixed and allowing the other segments design iteratively. As in Seg-VQ, in modified Seg-VQ the first principle component is used as a design reference for the initial line segment. However unlike Seg-VQ, in modified Seg-VQ the segment length of the first principle component is kept fixed at a fraction of the standard deviation of the projected input vectors onto the first principle component. The results show that by fixing the first segment at a proper length as a design scheme, Modified Seg-VQ improves the performance of Seg-VQ.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: constrained vector quantization; encoding complexity; data compression